Rwanda : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
Rwanda's Economic Development and Poverty Reduction Strategy provides a medium-term framework for achieving the country's long-term development goals and aspirations as embodied in Rwanda Vision 2020, the seven-year Government of Rwanda programme, and the Millennium Development Goals. The strategy promotes three flagship programs, namely sustainable growth for jobs and exports, poverty reduction by promoting pro-poor components of the national growth agenda, and providing an anchor for pro-poor growth by building on low incidence of corruption and a regional comparative advantage in soft infrastructure.